Different Combinations Of Legowo And Endemic Fish On Rice And Fish Productivity In Minapadi System: English - Farah Diana; Mahendra (Publisher Cv. Inara, 2021)
Minapadi is a fish rearing system in rice fields that is carried out with rice plants. This study aims to increase the income of farmers with high productivity of rice yields and increase the production of endemic fish. The method used is a Completely Randomized Design (CRD) experiment with 4 treatments and 3 replications. The treatments were: A1B1 (legowo 2:1 and giant prawns), A1B2 (legowo 2:1 and fish exclamation), A2B1 (legowo 4:1 and giant prawns), and A2B2 (legowo 4:1 and fish exclamation). This research was conducted for 90 days in the rice fields of Lango Village, Pante Ceureumen District, West Aceh Regency. Parameters observed were rice productivity, fish growth and business analysis. The results showed that the best treatment was A1B1 (legowo 4: 1 and giant prawns) by producing an average value of rice productivity of 5 kg/plot, and the average value of growth of giant prawns of 3.62 g/head and fish of fish of 37.17 g/head. From the results of this study, the application of the Minapadi system with giant prawns and fish with legowo 4:1 gave a positive impact on the observed parameters (P<0.05) and provided benefits for farmers.